(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This study delves into the nuanced dynamics of feedback in language acquisition, particularly for second language (L2) learners. It investigates how different types and timings of feedback impact learners' proficiency and motivation. The study underscores the importance of a balanced approach to feedback delivery, tailored to individual learner needs, to create a supportive learning environment conducive to maximizing learning outcomes. Educators can use these insights to refine their feedback strategies, ultimately contributing to more effective language instruction and improved learning experiences for L2 learners.